Alkyl pyrrolidone solvents N–methyl–2–pyrrolidone (NMP) and N–ethyl–2–pyrrolidone (NEP) in urine of children and adolescents in Germany – human biomonitoring results of the German Environmental Survey 2014–2017 (GerES V). (January 2021) - Schmied-Tobies, Maria I.H.; Murawski, Aline; Rucic, Enrico; Schwedler, Gerda; Bury, Daniel; Kasper-Sonnenberg, Monika; Koslitz, Stephan; Koch, Holger M.; Brüning, Thomas; Kolossa-Gehring, Marike
Highlights: Worldwide first representative data on exposure to NMP and NEP on national level. Metabolites of NMP were found in 100%, NEP in 87% of all urine samples. Higher NEP exposure of participants with low SES or migration background. Abstract: N -methyl-2-pyrrolidone (NMP) and its substitute N -ethyl-2-pyrrolidone (NEP) are aprotic solvents used in many technical applications, but also in carpets, and consumer products such as cleaning agents, and cosmetics. NMP and NEP are classified as reproductive toxicants. As a substance of very high concern (SVHC), NMP is included in the European REACH (Registration, Evaluation, Authorisation of Chemicals) candidate list for authorisation. NMP and NEP metabolites were measured in more than 2100 urine samples of 3- to 17-year-old children and adolescents, participating in the population-representative German Environmental Survey for Children and Adolescents 2014–2017 (GerES V). The two NMP metabolites 5-hydroxy- N -methyl-2-pyrrolidone (5-HNMP) and 2-hydroxy- N -methylsuccinimide (2-HMSI) could be detected and quantified in all urine samples, and the two NEP metabolites 5-hydroxy- N -ethylpyrrolidone (5-HNEP) and 2-hydroxy- N -ethylsuccinimide (2-HESI) in 32% and 87% of the urine samples. Geometric mean concentrations were 103.1 µg/L (88.21 µg/gcreatinine ) for the sum of NMP metabolites and 11.86 µg/L (10.15 µg/gcreatinine ) for the sum of NEP metabolites, thus remaining below the current health-based human biomonitoring values. For NMP, highest exposure was found in young children, but exposure pathways could not be revealed. Exposure to NEP was highest in adolescents and participants with low socio-economic status or migration background. Associations to usage of personal care products suggested the choice of products to have a distinct impact on NEP exposure. The presented data can be used by the German Human Biomonitoring Commission to derive new reference values (RV95) for NMP and NEP for children and adolescents in Germany. This will facilitate to recognise changing exposure levels in this population group in Germany.